Editorial for the Special Issue on Advanced Machine Learning Techniques for Sensing and Imaging Applications - Bihan Wen; Zhangyang Wang (Micromachines, 2022)
Recent advances in machine learning, from large-scale optimization to building deep neural networks, are increasingly being applied in the emerging field of computational sensing and imaging [...]